Crypto Assets Investment and Investor Protection: The Case of Malaysia and its Future Outlook - Nurulhuda MD NAZAR; Norshidah MOHAMED (Communications of International Proceedings, 2023)
This paper reports in-progress research on crypto assets investment and investor protection with specific reference to Malaysia. The paper uses literature survey approach to determine Malaysia’s status of investors’ protection of crypto assets investment and the future outlook of investor protection of crypto assets. Controversies have surrounded cryptocurrencies and crypto assets in countries with weak regulatory environments. As a country with predominantly Muslim population, Malaysia has been selected as the context of this research in view of its standing at the forefront of Islamic finance and emerging economic status. Regulatory initiatives have been crafted by the Securities Commission considering the interest and attention surrounding crypto assets investment. This paper implores further investigation on the seemingly inadequate investor protection framework related to taxation mechanism. Other challenges need addressing include investors’ education and awareness regarding crypto assets investment and the shortage of talent pool of Shariah-compliant digital market operators and digital fund-raisers
Keywords: Crypto Assets; Fintech; Digital Assets; Islamic Finance; Investor Protection